Evaluating the effect of biochar addition on the anaerobic digestion of swine manure: application of Py-GC/MS - Gómez, Xiomar; Meredith, William; Fernández, Camino; Sánchez-García, Mario; Díez-Antolínez, Rebeca; Garzón-Santos, Jorge; Snape, Collin E. (Springer, 2018)
The anaerobic digestion process of swine manure was studied when char was used as supplement for improving performance. The use of pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) was proposed for assessing the organic matter degradation. The assessment on biogas production was carried out using samples of swine manure (SM) supplemented with char in one case and pre-treated by microwave irradiation in the other. This experimental set-up allows for the comparison of the biological degradation observed under these two different configurations and therefore aids in understanding the effect of char particles on the process. Results showed similar performance for both systems, with an average improvement of 39% being obtained in methane production when compared to the single digestion of SM. The analysis of digestate samples by Fourier transform infrared (FTIR) spectroscopy and Py-GC/MS showed improved degradation of proteins, with the Py-GC/MS technique also capable of identifying an increase in microbial-derived material when char was added, therefore highlighting the relevant role of carbon conductive particles on biological systems. Py-GC/MS along with the use of FTIR spectroscopy has proven to be useful tools when evaluating anaerobic digestion.